Estudio socioeconómico de los vendedores y satisfacción de los usuarios de las ferias libres, como canal tradicional de comercialización de la ciudad Amaluza, año 2023. - Jaramillo Aguilar, Nixon Alexander (2024)
Free Fairs play an important role as a traditional trading channel. These markets, deeply rooted in the history and tradition of cities, not only serve as points of sale but also as places where different types of cultures and the economy of a population are reflected. Additionally, they are characterized by being held periodically, taking place weekly, and being located in areas with high foot traffic, offering fresh products at low prices. However, they depend on other producers. In this context, the aim of the present research was to determine the socioeconomic level of the vendors and the satisfaction level of the users of free fairs as a trading channel in the city of Amaluza in 2023. To achieve this, a mixed methodology was used, gathering both quantitative and qualitative data. The research applied both inductive and deductive methods, involving documentary, exploratory, and descriptive research. Various data collection techniques were employed, such as surveys and interviews, along with instruments like questionnaires and Google Forms. To assess user satisfaction, different service quality dimensions proposed by Hayes were used, while the socioeconomic level of the vendors was evaluated using dimensions suggested by the Instituto Nacional de Estadísticas y Censos (INEC). The results show that most of the vendors are women over the age of forty years and belong to a low socioeconomic level, as their income is below the unified basic salary (SBU), which allows them to cover basic services. On the other hand, users report being satisfied with the services provided by the free fair. Based on the 35 indicators applied, 86.64% agree that the prices are lower than in the market, 74.81% state that the sales points are clean, 80.15% find the products they want, 67.18% obtain quality products, and 70.99% are satisfied with the service. Furthermore, 73.66% report that there is good security. Keywords: Socioeconomic study, free fairs, customer satisfaction, marketing channels